Accurate SERS monitoring of the plasmon mediated UV/visible/NIR photocatalytic and photothermal catalytic process involving Ag@carbon dots. Issue 2 (24th December 2020) - Li, Linjia; Jin, Jing; Liu, Junjun; Yang, Jin; Song, Wei; Yang, Bai; Zhao, Bing
Abstract : The accurate SERS monitoring of a plasmon-mediated UV/visible/NIR photocatalytic and photothermal catalytic process on Ag@carbon dots has been demonstrated. Abstract : The excited carriers (electrons and holes) and heat energy that originate from plasmonic metal nanomaterials are crucial to the enhancement of the photocatalytic performance. In this study, an Ag@carbon dots (Ag@CDs) hybrid has been prepared with excellent Fenton-like photocatalytic and photothermal conversion properties for catalyzing H2 O2 to generate hydroxyl radicals (˙OH) for the degradation of crystal violet (CV) dye under full solar spectrum irradiation based on a unique plasmon effect. We have obtained some intrinsic kinetics information, including the reaction rate and apparent activation energy on the surface of the Ag@CDs, through a surface-enhanced Raman scattering strategy to investigate the contributions made by photocatalytic and photothermal effects in the plasmon mediated reaction under irradiation from ultraviolet (UV)/visible/near-infrared (NIR) light. In the visible light region, the Ag@CDs + H2 O2 system exhibits the fastest apparent reaction rate owing to the involvement of a large number of hot carriers, which are generated by the strongest plasmon effect, and the presence of the photothermal effect mediated by the plasmonic effect. As the wavelength of the illumination blue-shifts to the UV region, the plasmon effect is weakened, resulting in a decrease in the number of hot carriers. Furthermore, the hot carriers will not be further thermalized because of interband transitions. In addition, the catalytic performance of Ag@CDs in the NIR region is almost dominated by the photothermal effect. This work provides deep insights into understanding the plasmon-mediated photocatalytic mechanism of the Ag@CDs hybrid.